Provider-initiated vs. client-initiated HIV testing in Autonomous Province of Vojvodina, Serbia, 2000-2008 - Predrag Duric; Svetlana Ilic; Smiljana Rajčević (Journal of Infection in Developing Countries)
Background: This paper describes the changes in Human Immundodeficiency virus (HIV) testing rates in Autonomous Province (AP) Vojvodina, Serbia since 2000 and compares provider-initiated with client-initiated HIV testing. Methodology: Between 2000 and 2008, 66,327 HIV screening tests were reported from AP Vojvodina. During this time HIV testing rates increased from 1.2 per 1,000 inhabitants in 2000, to 7.7 per 1,000 inhabitants in 2008. Results: The results showed an increase in testing as a consequence of increased mandatory testing of surgical patients as well as an upsurge in the use of Voluntary Counselling and Testing (VCT).  Pregnant women that were tested represented less than 5% of the overall sample population. Conclusion: Public health efforts in AP Vojvodina to increase HIV testing rates lead to a continuous increase in testing rates, but with different limitations. HIV testing in low prevalence middle income countries could be highly affected by procurement difficulties, low motivation of medical professionals to initiate testing, and opportunities for testing limited to large towns and cities.